Is Fiscal Policy Procyclical in Developing Oil-Producing Countries? - Erbil, Nese (IMF Working Papers; Working Paper, 2011)
This paper examines the cyclicality of fiscal behavior in 28 developing oil-producing countries (OPCs) during 1990-2009. After testing five fiscal measures - government expenditure, consumption, investment, non-oil revenue, and non-oil primary balance - and correcting for reverse causality between non-oil output and fiscal variables, the results suggest that all of the five fiscal variables are strongly procyclical in the full sample. Also, the results are not uniform across income groups: expenditure is procyclical in the low and middle-income countries, while it is countercyclical in the high-income countries. Fiscal policy tends to be affected by the external financing constraints in the middle- and high-income groups. However, the quality of institutions and political structure appear to be more significant for the low-income group.